2014
DOI: 10.2174/1875399x010030100137
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Influence of Start Technique Preference for Elite Track Starters in Front Crawl

Abstract: Abstract:The aim of this study was to analyse the differences between preferential and non preferential start technique, and the inter-trial variability. Seven elite swimmers, who used track start as preferential technique, realised three trials in track and grab start. The kinematical analysis assessed the durations of the block, flight, entry, glide, leg kicking and full swimming phases to the 15-m mark. Aerial (sum of block and flight phase with head mark) and underwater (from entry to the head reach the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Many factors that affect start performance in swimming have been studied generally in adults ( Guimaraes and Hay, 1985 ; Holthe and McLean, 2001 ; Issurin and Verbitsky, 2002 ; Gautier et al, 2004 ; Galbraith et al, 2008 ; Vantorre et al, 2010 ; Puel et al, 2012 ). In several investigations, the anthropometric and biomechanical characteristics in pubertal swimmers have been studied ( Jürimäe et al, 2007 ; Latt et al, 2009 ; Latt et al, 2010 ); whereas in some of the studies, the relationship between these characteristics and swimming performance has been examined ( Klentrou et al, 1991 ; Siders et al, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors that affect start performance in swimming have been studied generally in adults ( Guimaraes and Hay, 1985 ; Holthe and McLean, 2001 ; Issurin and Verbitsky, 2002 ; Gautier et al, 2004 ; Galbraith et al, 2008 ; Vantorre et al, 2010 ; Puel et al, 2012 ). In several investigations, the anthropometric and biomechanical characteristics in pubertal swimmers have been studied ( Jürimäe et al, 2007 ; Latt et al, 2009 ; Latt et al, 2010 ); whereas in some of the studies, the relationship between these characteristics and swimming performance has been examined ( Klentrou et al, 1991 ; Siders et al, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly parameters used to compare the water phase of different start techniques included parameters related to the start performance (time to 5, 7.5, 10 or 15 m). Concerning to this, imperceptible differences were shown when the swimmers reached 5, 7.5 and 15 m. distance between the GS and TS (Benjanuvatra et al, 2004;Mason et al, 2007;Vantorre et al, 2010a). However, temporal advantages of .04, .15 and .14 s. were reported in the 5, 10 and 15 m. time, respectively, for the KS compared to the TS (Beretiae et al, 2012;Honda et al, 2010;Ozeki et al, 2012).…”
Section: Water Phasementioning
confidence: 99%
“…Both techniques (GS and TS) coexisted for more than forty years due to disagreements over their advantages and disadvantages. Several authors did not give priority to the use of one technique over another, concluding that the best start is the one most practiced by the swimmer (Blanksby, Nicholson, & Elliot, 2002;Mason, Alcock, & Fowlie, 2007;Vantorre, Seifert, Fernandes, Vilas-Boas, & Chollet, 2010a). Other investigations gave preference to the TS over the GS (Issurin & Verbitsky, 2002) or vice versa (Krüger, Wick, Hohmann, El-Bahrawi, & Koth, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of studies in the literature which consider horizontal and vertical impulses as predominant variables for the swim start (Blanksby, Nicholson, & Elliott, 2002;Vilas-Boas et al, 2003;West, Owen, Cunningham, Cook, & Kilduff, 2011). Benjanuvatra, Edmunds, and Blanksby (2007) and Vantorre et al (2011) argue that a high horizontal impulse is the primary basis for an optimal take-off from the block. Benjanuvatra et al (2007) found significantly higher horizontal impulses in expert swimmers as compared to beginners.…”
Section: Introductionmentioning
confidence: 99%